High-Fat Diet-Induced Neuropathy of Prediabetes and Obesity: Effect of PMI-5011, an Ethanolic Extract of Artemisia dracunculus L. - Pierre Watcho; Roman Stavniichuk; David M. Ribnicky; Ilya Raskin; Irina G. Obrosova (Mediators of Inflammation)
Artemisia species are a rich source of herbal remedies with antioxidant and anti-inflammatory properties. We evaluated PMI-5011, an ethanolic extract of Artemisia dracunculus L., on neuropathy in high-sfat diet-fed mice, a model of prediabetes and obesity developing oxidative stress and proinflammatory changes in peripheral nervous system. C57Bl6/J mice fed high-fat diet for 16 weeks developed obesity, moderate nonfasting hyperglycemia, nerve conduction deficit, thermal and mechanical hypoalgesia, and tactile allodynia. They displayed 12/15-lipoxygenase overexpression, 12(S)-hydroxyeicosatetraenoic acid accumulation, and nitrosative stress in peripheral nerve and spinal cord. PMI-5011 (500 mgkg-1d-1, 7 weeks) normalized glycemia, alleviated nerve conduction slowing and sensory neuropathy, and reduced 12/15-lipoxygenase upregulation and nitrated protein expression in peripheral nervous system. PMI-5011, a safe and nontoxic botanical extract, may find use in treatment of neuropathic changes at the earliest stage of disease.